Exploring, Maintaining, and Disengaging—The Three Phases of a Legislator's Life. Issue 3 (16th October 2017) - Bailer, Stefanie; Ohmura, Tamaki
Abstract : Building on the understanding that a career is a dynamic concept, this article applies the idea that parliamentarians' legislative activities vary according to their career stage and age. This is partly a function of experience and partly a function of future career prospects. Using a new data set of the German Bundestag (2002–13) that pinpoints the age and career stage of MPs at the time of individual activities, namely, attending votes, posing parliamentary questions, and holding rapporteurships, we identify practical and normative challenges to MPs' legislative work: It takes time to learn the trade and as the desire for re‐election dissipates, a last‐period problem arises. MPs significantly reduce their activity levels toward the end of their legislative careers, indicating a clear loss of accountability toward their parties and their constituents.